Effects of Tumor Necrosis Factor-Alpha Level in Peri-implanter Sulcular Fluid on Alveolar Bone Loss: A Prospective Study - Tekin, Gülüçağ Giray; Saribaş, Ebru Ece; Yokuş, Beran; Çolak, Mehmet; Özdemir Kaya, Eylem; Talo Yildirim, Tuba; Uysal, Ersin (Ataturk Universitesi, 2025)
Aim: The aim of this study was to investigate the possible relationships between periimplant sulcular fluid tumor necrosis factor alpha (TNF-?) levels and clinical parameters of periodontal disease and the amount of early alveolar bone loss in one-stage and two-stage implant systems. Method: Standard Plus (SP) one-stage implants were placed in 20 of 40 patients who were missing mandibular 1st molars while Bone Level (BL) two-stage implants were placed in the rest of 20 patients. In order to determine the periodontal status of each individual, Modified Plaque Index (mPI), Modified Gingival Index (mGI), Modified Sulcular Bleeding Index (mSBI), Probing Pocket Depth (PPD) and peri-implanter sulcular fluids (PISF) were recorded before prosthesis loading (month 0), 3rd and 6th months after prosthesis loading. Radiological evaluation was performed with computed tomography (CT) images prior to loading and 6 months after prosthesis loading. Results: In comparison, PPD values in the SP group are higher than in the BL group (P <.05). TNF-?, PPD values and rate of alveolar bone loss (ABL%) increased significantly between 0th and 6th month in terms of in-group evaluations in the SP group. In BL group, meaningful increases were observed in TNF-? and mSBI values between 0th and 6th months, in PISF volume between first 3 month period and first six month period. Conclusion: Predictable results were observed to be obtained in two different systems as laboratory clinically and radiologically. TNF-? levels were significantly increased in both groups. © 2025, Ataturk Universitesi. All rights reserved.
Peri-implanter Sulkuler Sıvıdaki Tümör Nekroz Faktörü-Alfa Seviyesinin, Alveolar Kemik Kaybına Etkileri: Prospektif Bir Çalışma
Keywords: alveolar bone loss; Dental implant; tumor necrosis factor alpha